PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTIONS KARYAWAN PADA BANK MEGA SYARIAH DI MAKASSAR - Andi Asirah; Djabir Hamzah; Idrus Taba (Jurnal Bisnis dan Kewirausahaan, 2016)
This study aims to: (1) to analyze the effect of job satisfaction on turnover intentions, and (2) to analyze the influence of organizational commitment on turnover intentions. The analytical method used is multiple regression analysis. This technique is used to analyze the influence of several independent variables on the dependent variable. Techniques of collecting data through observation, interviews and questionnaires. The population in this study were all employees at PT Bank Mega Syariah in Makassar. While the sample in this study were all (census) population study, the employees of Bank Mega Syariah, which amounted to 98 respondents. This study examined the effect of job satisfaction and organizational commitment to employee turnover intentions mega Islamic bank. Where R2 describes the significance, as well as the regression coefficient for the variable of job satisfaction is not a significant negative effect on turnover intentions and organizational commitment and constant regression coefficients significant impact on turnover intentions. Well test results; F-test and t-test showed a significant effect with probability = 0.00 <α 0.05. This means that Ho is rejected and H1 is accepted, so it is said to have a significant effect.